A Pragmatic Analysis of Deixis in the Film Damsel (2023) - Ika Rachma Widiarini (JALILA: Journal of Applied Linguistics and Literary Analysis, 2025)
This study aims to analyze the use of deixis in the film Damsel (2023) directed by Juan Carlos Fresnadillo, with a pragmatic approach. Damsel tells the story of Elodie, a young woman caught up in a royal conspiracy and struggling to survive and fight the threat of dragons. The main focus of this research is to explore how deixis is used to build relationships between characters, create cohesion in the narrative, and enrich the social and emotional themes present in the movie. This research uses a descriptive qualitative method to identify various types of deixis found in the dialog between characters in the film, namely deixis personalia, spatial, temporal, discourse, and social. The deixis theory used refers to Levinson (1983), which discusses how words and phrases used by characters function in their social and communication contexts. Through this pragmatic analysis, it is hoped that this research can provide new insights into the role of deixis in conveying messages in films and contribute to the understanding of communication structures in visual media.